Complications When Infusing Massive Distending Medium in Hysteroscopic Surgery: A Review of Preventions and Cures for Operative Hysteroscopy Intravascular Absorption Syndrome (OHIA) - Xia Cao; Xu Ding (Clinical and Experimental Obstetrics & Gynecology)
Objectives: Hysteroscopic surgery, as a minimally invasive gynecological diagnosis and treatment technique, has advantages including less trauma, quick recovery, and short hospital stay that are very common in clinical practice; however, certain problems remain. Using large amounts of distending medium can induce a series of body changes such as diluent hyponatremia, pulmonary edema and hypothermia. According to the 2021 Chinese Expert Consensus on anesthesia management for hysteroscopic diagnosis and treatment, the most common complication of hysteroscopic surgery was uterine perforation (0.12%), followed by operative hysteroscopy intravascular absorption syndrome (OHIA) (0.06%), intraoperative bleeding (0.03%), air embolism syndrome (0.03%), bladder or bowel injury (0.02%), and endometritis (0.01%). The incidence of uterine perforation and endovascular absorption syndrome was higher than others. With advances in both medical technology and devices, the incidence of uterine perforation has gradually decreased. Severe adhesions, multiple endometrial polyps, large uterine fibroids, etc., increase the difficulty of surgery, thus increasing operation time and the amount of fluid perfusion during surgery. OHIA has become the most important concern of clinicians during hysteroscopic surgery. At present, the prevention and treatment of OHIA remains to be further studied; accordingly, this article seeks to provide a review of current treatment modalities of OHIA during hysteroscopic surgery. Mechanism: Medline, Web of Science, and Ovid databases were searched using the following terms: distending medium, operative hysteroscopy, intravascular absorption syndrome; complications of hysteroscopic surgery. Findings in Brief: Shortening the operation time, reducing the volume of distending medium, decreasing infusion pressure, and using a bipolar scope can reduce the occurrence of OHIA during hysteroscopic surgery. Conclusions: Effective means of controlling and limiting OHIA during hysteroscopic surgery include: exploring the appropriate temperature of perfusion fluid; mastering the advanced monitoring methods; promoting the advanced surgical energy and perfusion system; and improving the surgical team’s understanding, diagnosis and treatment level of hysteroscopic surgical complications for the safety of perioperative patients’ vital signs.